Microspore embryogenesis in vitro: the role of stresses - T. I. Djatchouk; O. V. Khomyakova; V. N. Akinina; I. A. Kibkalo; A. V. Pominov (Вавиловский журнал генетики и селекции)
Gametic embryogenesis is one form of totipotency of plant cells, in which either male or female gametes are induced to form embryoids (sporophytes). Regeneration of haploid plants from embryoids and subsequent chromosome duplication result in doubled haploids and DH-lines. The production of haploids and doubled haploids (DHs) through gametic embryogenesis allows a single-stage development of complete homozygous lines from heterozygous plants. The development of effective haploid protocols to produce homozygous plants has a significant impact on plant breeding, shorting the time and costs required to establish new cultivars. There are several available methods to obtain haploids and DHs-lines, of which anther or isolated microspore culture in vitro are the most effective. Microspore embryogenesis is more commonly applied. This is in part because more male gametophytes are contained in a single anther compared to the single female gametophyte per embryo sac. Microspore embryogenesis is regarded as one of the most striking examples of plant cell totipotency. The switch of cultured microspores from gametophytic to sporophytic mode of development has been induced by stress treatments of various kinds applied to donor plants, inflorescences, buds, anthers or isolated microspores both in vivo and in  vitro. Physical or chemical pretreatments (cold and heat shock, sugar starvation, colchicine, n-butanol, gametocydes) act as a trigger for inducing the sporophytic pathway, preventing the gametophytic pathway development of microspore. The recent investigations have revealed that cold pretreatment during microspore reprogramming acts rather as an anti-stress factor alleviating the real stress caused by nutrient starvation of anthers or microspores isolated from donor plants. Under stress pretreatment a vacuolated and polarized microspore transformed into a depolarized and dedifferentiated cell, which is an obligatory condition for reprogramming their development. We summarize data concerning the role of various stresses in the induction of microspore embryogenesis and possible mechanisms of their action at cellular and molecular levels. Identification of new stresses allows creating efficient protocols of doubled haploid production for end-user application in the breeding of many important crops.